Insights into the promotion role of phosphorus doping on carbon as a metal-free catalyst for low-temperature selective catalytic reduction of NO with NH3. Issue 22 (31st March 2020) - Li, Weifeng; Jin, Shuangling; Zhang, Rui; Wei, Yabin; Wang, Jiangcan; Yang, Shuo; Wang, He; Yang, Minghe; Liu, Yan; Qiao, Wenming; Ling, Licheng; Jin, Minglin
Abstract : P species can effectively enhance the catalytic activity of carbon aerogels for NO reduction at low temperature. Abstract : The catalytic reduction of NO with NH3 (NH3 -SCR) on phosphorus-doped carbon aerogels (P-CAs) was studied in the temperature range of 100–200 °C. The P-CAs were prepared by a one-pot sol–gel method by using phosphoric acid as a phosphorus source followed by carbonization at 600–900 °C. A correlation between catalytic activity and surface P content is observed. The P-CA-800vac sample obtained via carbonization at 800 °C and vacuum treatment at 380 °C shows the highest NO conversion of 45.6–76.8% at 100–200 °C under a gas hourly space velocity of 500 h −1 for the inlet gas mixture of 500 ppm NO, 500 ppm NH3 and 5.0 vol% O2 . The coexistence of NH3 and O2 is essential for the high conversion of NO on the P-CA carbon catalysts, which can decrease the spillover of NO2 and N2 O. The main Brønsted acid sites derived from P-doping and contributed by the C–OH group at edges of carbon sheets are beneficial for NH3 adsorption. In addition, the C3 –PO configuration seems to have the most active sites for favorable adsorption and dissociation of O2 and facilitates the formation of NO2 . Therefore, the simultaneous presence of acidic groups for NH3 adsorption and the C3 –PO active sites for NO2 generation due to the activation of O2 molecules is likely responsible for the significant increase in the NH3 -SCR activity over the P–CAs. The transformation of C3 –PO to C–O–P functional groups after the reaction is found, which could be assigned to the oxidation of C3 –PO by the dissociated O*, resulting in an apparent decrease of catalytic activity for P-CAs. The C–O–P based functional groups are also active in the NH3 -SCR reaction.